Circulating immune complexes and mutations of HBsAg are associated with the undetectable HBsAg in anti-HBs and HBeAg positive occult hepatitis B virus infection - Yan, Ying; Sun, Huizhen; Chang, Le; Ji, Huimin; Jiang, Xinyi; Song, Shi; Xiao, Yingzi; Feng, Kaihao; Nuermaimaiti, Abudulimutailipu; Lu, Zhuoqun; Wang, Lunan (Frontiers in Microbiology, 2022)
Occult hepatitis B virus infection (OBI) is a HBsAg negative state in HBV infection with usually inactive HBV replication. However, there were a minority of individuals with positive HBeAg and anti-HBs among OBI blood donors and few studies have focused on this unusual serological pattern. We collected 2022 plasma of blood donors that preliminary screened reactive for HBV DNA and non-reactive for HBsAg from 16 provinces in China from 2015 to 2018. HBV DNA and HBsAg in these samples were retested using Cobas TaqScreen MPX test and ARCHITECT HBsAg Quantitative II assay. Lumipulse HBsAg-HQ assay and polyethylene glycol (PEG)-double precipitation following HCl and trypsin digestion were performed to detect HBsAg from HBsAg-anti-HBs circulating immune complexes (CICs). We found 1487 of 2022 samples were positive for Cobas HBV DNA test and non-reactive for ARCHITECT HBsAg assay, while 404 of them were positive using Lumipulse HBsAg-HQ assay. Totally, 10 HBsAg-/anti-HBs+/HBeAg+ OBI blood donor samples were further analyzed and HBsAg-CICs were detected in 7 samples. Sequence analysis of S region indicated that P127T, F134L, G145R, V168A and I126T/S mutations occurred in these samples. In conclusion, there were a minority of HBsAg-/anti-HBs+/HBeAg+ individuals in OBI blood donors. The undetectable HBsAg in these individuals was mainly due to HBsAg-CICs. Immune escape-associated mutations also happened under the host selective pressure. HBsAg dissociation methods or Lumipulse HBsAg-HQ assay is recommended to distinguish these individuals.